Percepción del familiar y calidad de cuidado de enfermería al paciente del servicio de emergencia del Hospital Belén de Trujillo - Rojas Rodríguez, Leyla Judith (2017)
This research was conducted in order to determine the relationship between the perception of family and quality of nursing care the patient's emergency service Bethlehem Hospital - Trujillo, descriptive, correlational, cross-sectional, during the months January to February, 2016 in the Bethlehem Hospital of Trujillo. The sample consisted of 100 family emergency service "Hospital Bethlehem - Trujillo" to data collection 2 instruments were used: the first instrument Perception of Family and second instrument quality nursing care. The data obtained were tabulated and presented in graphs and statistical tables single and double entry. The analysis of the relationship between the variables of study, a Chi-squared value p <0.00 is therefore highly significant was observed, so no relationship between "Perception of Family and Quality Nursing Care Patient Service Emergency Bethlehem hospital - Trujillo ", reached the following conclusions 66% of family members perceived favorably, 19% of relatives perceived indifferent and 15% perceived unfavorably, 6% of patients stated that the quality of nursing care was good, 94% of patients stated that quality of care And 0% of patients stated that the quality of nursing care is poor and that 6% of patients have a good quality of care and a favorable family perception, 0% of patients present a quality of good care and An indifferent family perception, and 0% of patients present good quality of care and unfavorable family perception; 60% of patients present a quality of regular care and a favorable family perception, 19% of patients present a quality of regular care and an indifferent family perception and 15% of patients present a quality of regular care and an unfavorable family perception ; 0% presents poor quality of care and favorable family perception, 0% presents poor quality of care and indifferent family perception, and 0% presents poor quality of care and unfavorable family perception.